2013
DOI: 10.1002/pro.2230
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interactions: General trends in the relationship between binding affinity and interfacial buried surface area

Abstract: Protein-protein interactions play key roles in many cellular processes and their affinities and specificities are finely tuned to the functions they perform. Here, we present a study on the relationship between binding affinity and the size and chemical nature of protein-protein interfaces. Our analysis focuses on heterodimers and includes curated structural and thermodynamic data for 113 complexes. We observe a direct correlation between binding affinity and the amount of surface area buried at the interface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
225
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(247 citation statements)
references
References 25 publications
17
225
0
5
Order By: Relevance
“…Recent work by Chen et al (32) has shown a positive correlation between binding affinity and the buried surface area at proteinprotein interfaces. We therefore explored the possibility of "artificially" increasing the buried surface area between CD47 and SIRP␣ as a means of increasing affinity.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work by Chen et al (32) has shown a positive correlation between binding affinity and the buried surface area at proteinprotein interfaces. We therefore explored the possibility of "artificially" increasing the buried surface area between CD47 and SIRP␣ as a means of increasing affinity.…”
Section: Resultsmentioning
confidence: 99%
“…93 Interfaces were filtered to only show those with more than 500 A^2 of surface area. 94 Structures which have a greater number of monomers in their asymmetric unit can show the same interface multiple times, and this is counteracted by only labeling each interface once. …”
Section: Analysis Of Crystal Structures To Discover Oligomerization Imentioning
confidence: 99%
“…In the cyt b 6 f structure from C. reinhardtii (PDB code 1Q90), residues 51-68 are buried within the hydrophobic domain of the membrane, implying a structure impediment to interaction with the Stt7 N-terminal domain, which is outside of the membrane in the p side aqueous phase. Moreover, the polyglycine hinge of the Rieske iron-sulfur protein subunit, proposed as a possible site of interaction between Stt7 and the cyt b 6 f complex, has a surface area of 340 Å 2 (PDB code 4OGQ), which is small compared with the most frequent range of interfacial surface areas for interprotein interactions of 500 -1000 Å 2 (42). Alternatively, significant in vitro kinase activity is demonstrated in this study with purified Stt7 kinase under reducing conditions, which implies a role for the p side cysteine residues Cys 68 -Cys 73 .…”
Section: Summary Of New Information Regarding the Properties Ofmentioning
confidence: 99%